Evaluation of Waste Management Policies in The City of Palangka Raya - Hari Nur Cahya Murni; Aswin Sebastian Hugo Silam (Westscience Press, 2024)
Waste in Palangka Raya City, Central Kalimantan Province is relatively worrying, because the condition of waste generation in 2021 last reached 53,990.25 tons and unmanaged waste that year was 1,018.06 tons (SIPSN 2022). Based on these problems, the Palangka Raya City Government has established an Environmental Management and Waste Management Policy through Palangka Raya City Regional Regulation No. 01 of 2017 concerning Waste Management and Cleanliness. The aim of this research is to determine and analyze waste management policies in Palangka Raya City. The research method used is descriptive qualitative. Data collection techniques are carried out through interview observation and documentation. The data analysis technique is carried out by reducing data, presenting data and drawing conclusions. In this regard, in terms of implementing 3R waste management in the City of Palangka Raya, unmanaged waste will be reduced significantly in accordance with the policies set by the Regional Government and the Palangka Raya City DPRD.